Nigerian Public Sector Governance Costs in the Era of President Muhammadu Buhari : an Administrative Perspective. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Digital Innovation : International Journal of Management, 2025)
The declaration by President Muhammadu Buhari that he is willing to reduce the rising expenses of managing public affairs is a major surprise. Newspapers everywhere have stated that he will face the confront the problem head-on by reforming numerous government agencies, merging others, and dismantling others. We are still figuring out the specifics. The only information that has been made public thus far is that the plan's first casualties will be the Universal Tertiary Matriculation Examination, the National Examinations Council, and the National Poverty Eradication Programme. It is evident from the announced strategy that the president and his officials either do not understand the seriousness of the issue or are once again manipulating a terrible sickness that is plaguing the nation. In what way would eliminating NECO and instructing WAEC to take on the personnel reduce costs? Or how would renaming NAPP contribute to improving governance value? How does he make sure that each and every Kobo that goes into counted national treasuries? What steps is he taking to guarantee that public policy is geared toward reducing people's suffering? The cost of governance during Jonathan's administration is examined in this study. It examines the cost of government from a thematic perspective, emphasizing its main points with specific examples. According to the paper's conclusion, the so-called clause of "senior ministers and junior or ministers of state" has led to the current unhealthy rivalry and widespread bitterness, but it has also resulted in needless waste of public funds in the payment of entitlements due to over-bloated administrative costs.